Identifying Dwarfs of MC Analog GalaxiEs (ID-MAGE): The Search for Satellites around Low-mass Hosts - Laura Congreve Hunter; Burçİn Mutlu-Pakdİl; David J. Sand; Paul Bennet; Donghyeon J. Khim; Denija Crnojević; Amandine Doliva-Dolinsky; Emmanuel Durodola; Catherine Fielder; Rowan Goebel-Bain; Michael G. Jones; Ananthan Karunakaran; et al. (The Astrophysical Journal)
We present results from Identifying Dwarfs of MC Analog GalaxiEs (ID-MAGE), a survey aimed at identifying and characterizing unresolved satellite galaxies around 35 nearby LMC- and SMC-mass hosts ( D  = 4−10 Mpc). We use archival DESI Legacy Survey imaging data and perform an extensive search for dwarf satellites, extending out to a radius of 150 kpc (∼ R _vir ). We identify 355 candidate satellite galaxies, including 264 new discoveries. Extensive tests with injected galaxies demonstrate that the survey is complete down to M _V  ∼ −9.0 (assuming the distance of the host) and μ _0, _V  ∼ 26 mag arcsec ^−2 (assuming an n  = 1 Sérsic profile). We perform consistent photometry, via Sérsic profile fitting, on all candidates and have initiated a comprehensive follow-up campaign to confirm and characterize candidates. Through a systematic visual inspection campaign, we classify the top candidates as high-likelihood satellites. On average, we find 4.0 ± 1.4 high-likelihood candidate satellites per LMC-mass host and 2.1 ± 0.6 per SMC-mass host, which is within the range predicted by cosmological models. We use this sample to establish upper and lower estimates on the satellite luminosity function of LMC-/SMC-mass galaxies. ID-MAGE nearly triples the number of low-mass galaxies surveyed for satellites with well-characterized completeness limits, providing a unique data set to explore small-scale structure and dwarf galaxy evolution around low-mass hosts in diverse environments.